Cardiomyocyte-Specific RIP2 Overexpression Exacerbated Pathologic Remodeling and Contributed to Spontaneous Cardiac Hypertrophy - Yang, Jing-jing; Zhang, Nan; Zhou, Zi-ying; Ni, Jian; Feng, Hong; Li, Wen-jing; Mou, Shan-qi; Wu, Hai-ming; Deng, Wei; Liao, Hai-han; Tang, Qi-zhu (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to investigate roles and mechanisms of Receptor interacting protein kinase 2(RIP2) in pressure overload induced cardiac remodeling. Human failing or healthy donor hearts were collected for detecting RIP2 expression. RIP2 cardiomyocyte specific overexpression, RIP2 global knockout or wild type mice were subjected to sham or aortic banding (AB) surgery to establish pressure overload induced cardiac remodeling in vivo. PE treated neonatal rat cardiomyocytes (NRCMs) were used for further investigation in vitro. RIP2 was up-regulated in failing human hearts, remodeling mouse heart and Ang II treated NRCMs. RIP2 overexpression aggravated pressure overload induced cardiac remodeling. Mechanistically, RIP2 overexpression significantly activated phosphorylation of TAK1, P38 and JNK1/2. Inhibiting TAK1 activity by its specific inhibitor completely prevented cardiac remodeling attributed to RIP2-overexpression. This study further confirmed that RIP2 overexpression in NRCM could exacerbate PE induced NRCM hypertrophy, however, TAK1 silence by specific siRNA could completely rescue the RIP2-overexpression mediated cardiomyocyte hypertrophy. Moreover, we showed that RIP2 could bind to TAK1 in HEK293 cells, and PE could promote interaction of RIP2 and TAK1 in NRCM. Given the powerful deterioration of RIP2 overexpression, we also exhibited that RIP2 overexpression caused spontaneous cardiac remodeling at the age of 12 months and 18 months. Finally, we also indicated that RIP2 global attenuated pressure overload induced cardiac remodeling via reducing TAK1/JNK1/2/P38 phosphorylation. Taken together, RIP2 mediated phosphorylation activation of TAK1/P38/JNK1/2 signaling exacerbated pressure overload induced cardiac remodeling and caused spontaneous cardiac remodeling, RIP2 inhibition might be a potential strategy for preventing cardiac remodeling.